La metáfora mecánica y biopsíquica en el análisis organizacional (Estudios) - Abad Merchán, Guido Andrés (2018)
The aim of this article is to reflect on the organizational analysis based on metaphors following the line of Gareth Morgan and two of them are proposed that compare the organization, either as a machine or as a biopsychic organism, in order to have a better understanding of the adaptive dynamics that organizations have with their environment. The metaphor is an instrument that helps the understanding of contemporary organizations characterized by a high degree of complexity and that are being affected by a changing and increasingly uncertain environment. It also raises the idea of a double metaphor of the organization: as if it were a machine and a biopsychic organism simultaneously.